A gênese teórica da concepção habermasiana de esfera pública - Campato, Roger Fernandes (Universidade Federal de São Carlos, 2002)
This dissertation aims to discuss the theoretical sources taken by Jürgen Habermas to legitimate his concept of public sphere (Öffentlichkeit). The study also presents alternative interpretive perspectives to the one assumed by Habermas in The Structural Transformation of the Public Sphere (Strukturwandel der Öffentlichkeit).
Keywords: Ética política; Habermas, Jürgen, 1929-; Teoria crítica; Opinião pública; Ciência política - filosofia; Mudança social; Jürgen Habermas; Critical theory; Political philosophy; Public opinion; Public sphere; The structural transformation of the public; CIENCIAS HUMANAS::FILOSOFIA